Functional mechanism of neuroprotection by inhibitors of type B monoamine oxidase in Parkinson''s disease. (August 2009) - Naoi, Makoto; Maruyama, Wakako
Neuroprotective therapy has been proposed for age-related neurodegenerative disorders, including Parkinson''s disease. Inhibitors of type B monoamine oxidase (MAOB-Is), rasagiline and (-)deprenyl, are the most promising candidate neuroprotective drugs. Clinical trials of rasagiline in patients with Parkinson''s disease suggest that rasagiline may have some disease-modifying effects. Results using animal and cellular models have proved that the MAOB-Is protect neurons by the intervention of ''intrinsic'' mitochondrial apoptotic cascade and the induction of prosurvival antiapoptotic Bcl-2 and neurotrophic factors. Rasagiline-related MAOB-Is prevent mitochondrial permeability transition induced by various insults and activation of subsequent apoptotic cascades: cytochrome c release, casapase activation, and condensation and fragmentation of nuclear DNA. MAOB-Is increase transcription of prosurvival genes through activating the nuclear transcription factor-(NF) system. Rasagiline increases the protein and mRNA levels of GDNF in dopaminergic SH-SY5Y cells, whereas (-)deprenyl increases those of BDNF. Systemic administration of (-)deprenyl and rasagiline increases these neurotrophic factors in the cerebrospinal fluid from patients with Parkinson''s disease and nonhuman primates. This review presents recent advances in our understanding of the neuroprotection offered by MAOB-Is and possible evaluation of neuroprotective efficacy in clinical samples is discussed.